Communication Strategies in Islamic Da'wah Opportunities and Challenges in the Era of Artificial Intelligence - Marlina; Yaza Azahra Ulya (PT Agung Media Publisher, 2024)
The integration of artificial intelligence (AI) into communication strategies has revolutionized various fields, including Islamic Da'wah. This study explores how AI technologies can be utilized to enhance the dissemination of Islamic teachings, examining both the opportunities and challenges this integration presents. This research employs a mixed-methods approach, combining qualitative analysis of AI applications in religious contexts with quantitative surveys of Da'wah practitioners and their audiences. The findings reveal that AI technologies, such as chatbots, natural language processing, and machine learning, significantly enhance the reach and personalization of Da'wah efforts. AI enables interactive and engaging communication, breaking down geographical and linguistic barriers. However, the results also highlight several challenges, including ethical concerns regarding the accuracy of AI-generated content, the potential for misinformation, and the digital divide that limits access to these technologies. The study concludes that while AI offers substantial opportunities to innovate Islamic Da'wah, careful consideration must be given to ethical implications and practical limitations. The collaboration between AI experts and Islamic scholars is essential to ensure that AI-driven Da'wah initiatives are both effective and respectful of Islamic values. Balancing AI's advantages with its challenges can lead to more effective and inclusive communication strategies in the digital era, ultimately enriching the practice of Islamic propagation.